Proses Kegiatan Sponsorship pada Event Royal Jogja Sand Dunes Geospatial Run 2019 - Desy Nurelya; Heri Setyawan (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
The research problems of this study is how to sponsor activities in an effort to establish business cooperationbetween events and sponsors target of The Royal Jogja Sand Dunes Geospatial Run 2019. The objectives of thisstudy is to study the process of sponsorship activities at The Royal Jogja Sand Dunes Geospatial Run 2019. Thistype of research is a descriptive qualitative research by collecting, processing and presenting data obtained in theform of complete and correct information. Data collection techniques used in this study were the method ofobservation, interviews and documentation. The results show that the process of sponsoring activities carried out atThe Royal Jogja Sand Dunes Geospatial Run 2019 through several examples, namely: 1) preparing sponsorshipactivities from starting to make proposals, determining the target sponsors, communicating with sponsors, holdingmeetings with sponsors. with the agreement of cooperation; 2) carrying out sponsorship activities, namelycontrolling control and service to sponsors; 3) evaluation and feedback on sponsorship activities, namely sendingfinal report documents and re-establishing communication with the sponsor.